2015
DOI: 10.1021/acs.est.5b00833
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Mediated Effects of Antibiotics on Daphnia Nutrition

Abstract: In polluted environments, contaminant effects may be manifested via both direct toxicity to the host and changes in its microbiota, affecting bacteria-host interactions. In this context, particularly relevant is exposure to antibiotics released into environment. We examined effects of the antibiotic trimethoprim on microbiota of Daphnia magna and concomitant changes in the host feeding. In daphnids exposed to 0.25 mg L(-1) trimethoprim for 24 h, the microbiota was strongly affected, with (1) up to 21-fold decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 72 publications
2
60
0
Order By: Relevance
“…to be the dominant taxon, this is in accordance with earlier studies who also found this taxon to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;Gorokhova et al, 2015). However, by specifically characterizing the gut microbiota, we found that in our cultures Aeromonas sp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…to be the dominant taxon, this is in accordance with earlier studies who also found this taxon to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;Gorokhova et al, 2015). However, by specifically characterizing the gut microbiota, we found that in our cultures Aeromonas sp.…”
Section: Discussionsupporting
confidence: 93%
“…Its presence furthermore enabled the uptake of protein macromolecules and influenced gut motility (Bates et al, 2006). Interestingly, Gorokhova et al (2015) found a strong decrease in feeding activity, digestion efficiency and carbon uptake in Daphnia of which the gut microbiota was affected by antibiotic exposure. Possibly, Aeromonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…stimulation of fungal activity following inhibition of bacterial growth (Rousk et al, 2008). Alternatively, antibiotics may indirectly affect animal nutrition and, ultimately growth, via direct effects on their gut microbiota (Gorokhova et al, 2015). We encourage more basic research on how antibiotics may disturb food webs and affect the structure and function of the immediate ecosystem.…”
Section: Environmental Modulation Of Toxicity and Ecosystem-wide Riskmentioning
confidence: 99%
“…Antibiotics can alter the microflora in the gut of invertebrates and consequently their efficiency to assimilate nutrients and energy from the ingested food. For instance, Gorokhova et al (2015) observed a lower diversity in the gut microflora that was associated with a lower assimilation efficiency in Daphnia magna exposed to one of the antibiotics assessed in the present study (trimethoprim) and at a similar concentration (250 ”g/L). Such impacts on the gut microflora could explain the lack of growth observed for G. fossarum exposed to 200 ”g/L of the antibiotic mixture, if the ability of G. fossarum to profit from a potentially higher food quality was lost at this high antibiotic concentration.…”
Section: Discussionmentioning
confidence: 48%